The Impact of Toll Roads on The Modes Choice Transportation Case Study: Banyuwangi-Surabaya - Idham Kholid, Moh. Abda Ghoits; Herijanto, Wahyu (Institut Teknologi Sepuluh Nopember, 2024)
As the population increases, the level of activity and mobility will also increase. To facilitate people's movement, the Indonesian Government built infrastructure in the form of toll roads. The Trans-Java Toll Road stretches between Merak Harbor, Cilegon, Banten Province, and Ketapang Harbor, Banyuwangi, East Java Province. The Surabaya-Banyuwangi section is currently in the development stage. The existence of the Banyuwangi-Surabaya toll road will impact behavioural patterns in using transportation modes. Currently, several modes of land transportation can be used, i.e., buses via toll and non-toll (economy), trains, and private cars. The current travel time from Banyuwangi-Surabaya is 6 hours 30 minutes using a toll bus and 8 hours 15 minutes using a non-toll bus. In comparison, the travel time for the Wijayakusuma train mode (Banyuwangi-Surabaya) is 6 hours 2 minutes. Private vehicles (cars) also use a variety of different routes, causing the travel time and travel costs of private cars to be affected. Differences in travel time and routes used due to the existence of the Banyuwangi-Surabaya toll road change mode preferences between toll buses, non-toll buses (economy), trains, and private vehicles (cars). This research is a model for selecting transportation modes for the Banyuwangi-Surabaya route using the split modal method with an exponential function or difference function (β) with a value of NMAE= 0.0000087, where the NMAE value is close to 0, and can be used to estimate the proportion of modal choices on the Banyuwangi Surabaya route.